Features of Organizational and Educational Practice in Distance Format (the Case of the Department of Education and Innovative Pedagogy at H.S. Skovoroda KHNPU) - Esikova, Iryna (Educological discourse, 2024)
The New Ukrainian School requires a new teacher who is motivated and effective as an agent of educational transformations, as a researcher and creator with a focus on continuous professional and personal growth throughout his career, ready to improvise and experiment. Pedagogical practice has the most significant influence on professional development of a teacher in the process of training. It is an integral and important link in the professional development of higher education students, and its completion is the leading stage in the practical application of the acquired theoretical knowledge. Taking into account the challenges of today, higher education institutions have to review the forms, content and means of pedagogical management and educational practice. One of the important tendencies in Ukrainian education is the use of digital applications (Sanva, Reardeck, Genial, Emaze, Fiverr Logo Design, Wix Logo Maker, Looka, Quizalize, Kahoot, JeopardyLabs, FlipQuiz, Learningapps, Rebus) and creating own case of tools. The article analyses the experience of the Department of Educational Studies and Innovative Pedagogy at H.S. Skovoroda Kharkiv National Pedagogical University as a case study of training applicants for the first (bachelor) level of higher education in specialties 014.04 Secondary Education (Mathematics), 014.06 Secondary Education (Chemistry), 014.08 Secondary Education (Physics), 014.09 Secondary Education (Informatics) in a forced distance education. Its purpose is disclosed, a list of digital applications for active interaction with applicants, the effectiveness of tasks and examples of application use are given. Specific tools and services, in particular artificial intelligence for use in the educational process, are analysed. It is outlined that the problem of organising pedagogical practices is urgent and requires methodological research and practical approbation of applications, studying the peculiarities of their work in the distance learning format.